2008
DOI: 10.1159/000164685
|View full text |Cite
|
Sign up to set email alerts
|

Elective Use of Aortic Balloon Occlusion in Cesarean Hysterectomy for Placenta Previa Percreta

Abstract: Background: Only few reports are available on the use of aortic balloon catheter for cesarean hysterectomy in placenta previa percreta. Case: A 32-year-old woman with placenta previa percreta underwent cesarean hysterectomy at 34 weeks of gestation. Before starting the surgery, an aortic occlusion balloon catheter (30 mm balloon, 5 Fr) was inserted. For total hysterectomy, the aortic balloon catheter was inflated and there was a sudden and dramatic reduction in blood loss, and the surgery was completed safely.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 10 publications
1
66
1
2
Order By: Relevance
“…Patient characteristics, anaesthetic and surgical details and fetal data are shown in Table 1. General anaesthesia was used in 38 patients with mean induction-to-delivery interval 4.2 min [range [3][4][5][6][7][8][9][10][11][12] and mean time from induction to first balloon inflation 5.8 min [range [4][5][6][7][8][9][10][11][12][13]. Epidural anaesthesia was used in seven patients of whom three required conversion to general anaesthesia (two patients for inability to cope and one patient for insufficient analgesia).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient characteristics, anaesthetic and surgical details and fetal data are shown in Table 1. General anaesthesia was used in 38 patients with mean induction-to-delivery interval 4.2 min [range [3][4][5][6][7][8][9][10][11][12] and mean time from induction to first balloon inflation 5.8 min [range [4][5][6][7][8][9][10][11][12][13]. Epidural anaesthesia was used in seven patients of whom three required conversion to general anaesthesia (two patients for inability to cope and one patient for insufficient analgesia).…”
Section: Resultsmentioning
confidence: 99%
“…7,8 However, reports of abdominal aorta balloon occlusion have been published. [9][10][11][12] In this case series, we present our experience with prophylactic lower abdominal aorta balloon occlusion (PABO) in the management of 45 women with morbidly adherent placenta undergoing caesarean section. The efficacy, risks and benefits of this technique as well as the anaesthetic management are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-aortic balloon occlusion has become a viable approach for the management of anticipated postpartum hemorrhage in cases such as placenta percreta. 23 This has typically required preoperative planning with placement of Hemorrhage During Gynecologic Surgery 725 www.clinicalobgyn.com an infrarenal intra-aortic balloon under fluoroscopic guidance before the surgery. Once placed, the balloon can be intermittently inflated during the surgery to allow temporary occlusion of the distal aorta and significant reduction in hemorrhage in the pelvis.…”
Section: Intra-aortic Balloon Occlusionmentioning
confidence: 99%
“…Significant decreases in the incidence of hysterectomy were noted, blood loss was minimal, and no IABO-related complications were found. In some cases, the aorta BC is superior to catheterization of the internal iliac arteries, which is more complex to dislodge and for which complete control of bleeding is difficult to achieve [13]. Thus, it was more commonly used in placenta previa to control serious intraoperative bleeding.…”
mentioning
confidence: 99%
“…Qu et al [15] had observed that safe time limits in various levels of abdominal aorta clamping, including high level (T12 level, above the celiac trunk artery), medium level (L2, above the renal artery), and low level (L4, above the common iliac artery) were between 25 minutes and 30 minutes. However, Masamoto et al [13] reported a case of aortic balloon occlusion in CH for placenta percreta, in which the aortic occlusion was sustained for 80 minutes. The duration of aortic loop ligation was 30 minutes, which is within the recommended safe time limit, and no postoperative complication was found.…”
mentioning
confidence: 99%